Prevalence and correlates of mental health symptoms and well-being among elite sport coaches and high-performance support staff - Pilkington, V.; Rice, S. M.; Walton, C. C.; Gwyther, K.; Olive, L.; Butterworth, M.; Clements, M.; Cross, G.; Purcell, R. (Sports Medicine - Open, 2022)
Background: There is growing understanding of mental health needs in elite athletes, but less is known about the mental health of coaches and support staff who work within elite sport settings. This study examined the prevalence and correlates of mental health symptoms in elite-level coaches and high-performance support staff (HPSS) and compared rates against published elite athlete samples. A cross-sectional, anonymous, online survey was administered to coaches and HPSS working in Australia`s high-performance sports system. Main outcomes were scores on validated measures of psychological distress, probable `caseness` for a diagnosable psychological condition, alcohol consumption and sleep disturbance. Results: Data were provided by 78 coaches (mean age = 46.4 years, 23.8% female) and 174 HPSS (mean age = 40.0 years, 56.7% female). Overall, 41.2% of the sample met probable caseness criteria, 13.9% reported high to very high psychological distress, 41.8% reported potential risky alcohol consumption and 17.7% reported moderate to severe sleep disturbance, with no statistically significant differences between coaches and HPSS. The most robust correlates of psychological distress and probable caseness were dissatisfaction with social support and dissatisfaction with life balance, while poor life balance was also associated with increased alcohol consumption and poor social support with sleep disturbance. Coaches and HPSS reported similar prevalence of mental health outcomes compared to rates previously observed in elite athletes, with the exception of higher reporting of alcohol consumption among coaches and HPSS. Conclusions: Elite-level coaches and HPSS reported levels of psychological distress and probable caseness similar to those previously reported among elite-level athletes, suggesting that these groups are also susceptible to the pressures of high-performance sporting environments. Screening for mental health symptoms in elite sport should be extended from athletes to all key stakeholders in the daily training environment, as should access to programs to support mental health and well-being.